Development of Character Education Models in Madrasas Through the Establishment of the Tahajud Prayer - Supendi, Pepen; Palah; Hasanah, Aan (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This study aimed to examine and explore the development of student character education models through habituation of programmed tahajud prayers in MTs As-Sa'idah. This research uses a qualitative approach with descriptive methods. Data collection techniques are interviews, observation, and study of literature. The results of this study, are: First, the reality of education in the inheritance of the values ​​of character education through the process of habituating the programmed prayer; Second, the tahajud prayer is a character inheritance model that is able to preserve the values ​​of the Sunnah of the Prophet Muhammad. The inheritance model of character education through habituation of tahajud prayer are: 1) focus, derived from the doctrine of the Qur'an and Sunnah; 2) Procedure, using a direct learning model. And the Third, the character values ​​that can be implemented as a basis for character building show in 9 of character values.